ANALISIS MANAJEMEN RISIKO OPERASIONAL DI LABORATORIUM RSUD MAJALENGKA - Naue, Vivi Anggriani; Dermawan, Asep; Yuliansyah SM, Yuliansyah SM; Wiryanti, Wiwin (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2024)
Background: Clinical laboratory is a medical laboratory which provide services for clinical specimen examination in order to get personal health information mainly to confirm a diagnose, to cure a disease and recover the health. Based on the incident report in RSUD Majalengka during 2020, there were 3 laboratory personils slipped to injured, 2 people pricked by a needle, and the latest report showed there was 1 person infected by tuberculosis. Risk management is developed to minimize work accident risk and also occupational borne disease for health workers especially in laboratories. This study was aimed to identify operational risk, analyze the risk level and to determine operational risk control in the laboratory of RSUD Majalengka. Methods: This was a descriptive qualitative and quantitative study with observation through interviews with 21 MLTs in the laboratory of RSUD Majalengka, Results: The results showed 12 operational risks with a low risk of 17%, a medium risk of 75% and a high risk of 8%. The control carried out on operational risks is in the form of controls that aim to reduce the possibility of substitution, technical control, administrative control and the use of PPE. Conclusion: in the laboratory of RSUD Majalengka has carried out controls, but to see the effectiveness of these controls, regular monitoring and evaluation needs to be carried out. Keywords : Risk, Occupational Health dan Safety, laboratory